An Analysis of a Teacher's Code Switching inan Englishas a Foreign Language (EFL) Classroom (A Case Study at a Junior High School in Bandung) - Fadholi, Muslikha (2015)
The present study is entitled An Analysis of a Teacher's Code Switching in an English as a Foreign Language (EFL) ClassroomA Case Study at Junior High School in Bandung. It investigates the types of code switching in the EFL classroom, finds out the reasons of the teacher for using code switching in the EFL classroom and analyses the students' perception toward the teacher's switching in the EFL classroom. This study involved a male English teacher and 35 students as respondents who were chosen based on their English score. The obtained data were classified based on Poplack's theory (2012). The study reveals that the types of code switching found in the EFL classroom were tag-switching, inter-sentential switching and intra-sentential switching. Furthermore, the reasons of the teacher for using code switching were students' background and mixed ability, ease of communication, explaining and translating the unknown term, students' facial expression, explaining grammar and vocabulary, habitual usage, managing class and repetition for clarification. The students' perception toward the teacher's switching give their positive perception toward teacher's switching in the classroom. Students agreed that code switching has a great benefit in term of increasing their vocabulary.---------- Penelitian ini berjudul analisa alih kode guru di kelas EFL. Studi kasus di sekolah menengah pertama di Bandung. Penelitian ini membahas tentang tipe-tipe dari alih kode di kelas EFL, mencari tahu tentang alasan guru melakukan alih kode di kelas EFL, dan menganalisa persepsi siswa mengenai alih kode yang dilakukan oleh guru di kelas EFL. Penelitian ini melibatkan seorang guru Bahasa Inggris dan 35 siswa sebagai responden yang dipilih berdasarkan nilai Bahasa Inggris di kelas. Data yang diperoleh di klasifikasikan berdasarkan teori Poplack (2012). Penelitian ini menunjukan bahwa tipe-tipe dari alih kode yang ditemukan di kelas EFL adalah tag-switching, inter-sentential, dan intra-sentential. Kemudian alasan dari guru untuk melakukan alih kode di kelas EFL diantaranya latarbelakang siswa dan kemampuan siswa yang berbeda beda, kemudahan dalam berkomunikasi, menerangkan dan menerjemahkan kata yang asing, ekspresi muka siswa, menerangkan grammar dan kata-kata, terbiasa menggunakan, mengatur kelas dan pengulangan untuk klarifikasi. Persepsi siswa mengenai alih kode yang dilakukan oleh guru memberikan pandangan positif mengenai alih kode yang dilakukan oleh guru di kelas.